Teachers as Soft-Prevention Actors: Wasatiyyah and School-Based Resistance to Youth Radicalization in Indonesia - Muhammad Faishol; Wasino; Fakhruddin; Asrori (MUMTAZ : Jurnal Pendidikan Agama Islam, 2026)
This study addresses the critical role of schools in early-stage prevention of youth radicalization, focusing on the underexplored domain of everyday pedagogical practices within Islamic Religious Education (IRE). It positions IRE teachers as key soft-prevention agents whose daily interactions and theological interpretations can build micro-level resilience among students. Employing a phenomenological approach, this research is based on fieldwork involving 26 IRE teachers in Banyuwangi, Indonesia, utilizing semi-structured interviews, classroom observations, and document analysis. The findings identify four core pedagogical strategies that constitute preventive practices: contextualizing sacred texts, character-focused instruction, modeling inclusive behavior, and engaging with the wider community. While these strategies generate significant resilience mechanisms capable of interrupting early radicalization pathways, their effectiveness is moderated by structural constraints, including limited professional development, inequitable access to certification, and ideological contradictions within schools and communities. By integrating the Islamic ethical concept of wasatiyyah (moderation) with established radicalization frameworks, this study contributes to scholarly debates on culturally embedded prevention and specifies the institutional conditions necessary for teacher agency to effectively support resilience-building in plural societies. This article draws on data from a broader phenomenological study of IRE teachers’ practices in Banyuwangi, but specifically analyzes their role in preventing radicalization through the lens of wasatiyyah and soft prevention frameworks.